Water exchange on seven-coordinate Mn(II) complexes with macrocyclic pentadentate ligands: Insight in the mechanism of Mn(II) SOD mimetics - Dees, Anne; Zahl, Achim; Puchta, Ralph; van Eikema Hommes, Nico; Heinemann, Frank Wilhelm; Ivanovic-Burmazovic, Ivana (Inorganic Chemistry, 2007)
Seven-coordinate manganese(II) complexes [Mn(L)(HO) ], where L represents an equatorial pentadentate macrocyclic ligand with five nitrogen donor atoms, were studied with regard to their acid-base properties, water-exchange rate constants, and corresponding activation parameters (ΔH, ΔS, and ΔV). Three of the studied complexes without imine bonds in the macrocyclic ligand are proven superoxide dismutase (SOD) mimetics. Their water-exchange parameters were compared with those of the imino groups containing complex [Mn(L1)(Cl)] (dichloro-2,13-dimethyl-3,6,9,12,18- pentaazabicyclo[12.3.1]-octadeca-1(18),2,12,14,16-pentaenemanganese(II)), which does not show SOD activity. In addition the X-ray crystal structure of a new complex, dichloro-2,6-bis[1-(2-(N-methylamino)-ethylimino)ethyl]pyridine- manganese(II) [Mn(L2)(Cl)], which is the acyclic analog of [Mn(L1)(Cl)], is reported. Stability constants of the complexes and the pK values of the ligands were measured by potentiometric titration. The titrations of [Mn(L1)(HO)] and [Mn(L2)(HO)] led to complicated species distribution curves because of their ligands containing imine bonds. Water exchange was measured by temperature- and pressure-dependent O NMR techniques. In addition to the measurements on [Mn(EDTA)(HO)] and its derivatives, this is the only study of water exchange on seven-coordinate manganese complexes. The water exchange rate constants vary between 1.6 × 10 s and 5.8 × 10 s at 25°C and are mainly controlled by the π-acceptor abilities of the ligands. The exchange rate constant of the diaqua-1,4,7,10,13- pentaazacyclopentadecanemanganese(II) [Mn([15]aneN)(H O)] complex seems to be even higher but could not be exactly determined. On the basis of the obtained activation parameters, the exchange mechanism of the studied seven-coordinate manganese(II) complexes follows a dissociative pathway (I mechanism). DFT calculations (UB3LYP/LANL2DZp) were performed to obtain the energy required for the dissociation of the coordinated water molecule, that is, the energy difference between the starting seven-coordinate complex and a six-coordinate intermediate. The results have been discussed in terms of the catalytic mechanism of the proven SOD mimetics. © 2007 American Chemical Society.